White-light emitting diodes' spectrum effect on photosynthesis and nutrient use efficiency in Podocarpus macrophyllus seedlings. (30th July 2020) - Luo, Yunqing; Zhao, Shujie; Tang, Jingyao; Zhu, He; Wei, Hongxu; Cui, Wei; Wang, Minghui; Guo, Peng
Abstract: Fast urbanization and population increase resulted in the demand for ornamental seedling supply in a high efficiency under the culture of continuous artificial lighting. Light emitting diode (LED) can be considered as the replacement of high-pressure sodium (HPS) lamps by providing lights with specific wavelengths for plant growth at low energy cost. In this study, nutrient use efficiency was detected in Podocarpus macrophyllus seedlings under lighting spectra generated by white light-emitting diodes (LEDs) (red (R)/green (G)/blue (B)=8.4:75:16.6) and high-pressure sodium (HPS) lamps (R/G/B/=4.3:69.3:26.5). Compared to seedlings under the HPS spectrum, those under white LED spectrum had better growth, greater biomass accumulation, higher photosynthesis and gas exchange. In contrast, LED-spectrum treated seedlings had greater nitrogen (N) and phosphorus (P) contents than HPS-spectrum treated ones. The LED spectrum promoted nutrient use index for both N and P in seedlings compared to the HPS spectrum. The LED spectrum induced steady-state uptake of P but resulted in the dilution of N. In conclusion, white LED can be considered to replace the usage of HPS lamps for the culture of tree seedlings due to the spectrum effect on N utilization, P uptake and the use efficiencies of N and P.